EMPLOYEE WORK MOTIVATION ANALYSIS AT SUMEDANG SAPPHIRE HOME HOTEL - Muhammad Irfan Nur’Arif (SINTESA, 2023)
This research is motivated by the existence of problems in the implementation of work motivation analysis at Hotel Sapphire Home Sumedang, including employees who are still less than optimal. This qualitative study aims to obtain an overview of howwork motivation and efforts to provide work motivation are for employees of HotelSapphire Home Sumedang. The research method used is descriptive qualitative with moredescriptions of the results of interviews, direct observation, and documentation. Meanwhile, data analysis uses the Miles and Huberman model with data reduction,data presentation and data verification methods. The results showed that theimplementation of work motivation analysis on the employees of Hotel SapphireSumedang was still not optimal, which was marked by the lack of self-actualization needs.Nevertheless, there are four aspects of work motivation analysis that have been appliedquite well, namely physical and biological needs, safety and security needs, social needs,and the need for respect or prestige. Suggestions that can be used in an effort to providework motivation at the Sapphire Home Hotel Sumedang are through understanding the behavior of subordinates, behaving realistically, with different levels of needs, being ableto use expertise, providing motivation that refers to people, and giving examples.